2020
DOI: 10.1108/cms-08-2019-0304
|View full text |Cite
|
Sign up to set email alerts
|

Can multiple large shareholders promote corporate social responsibility?

Abstract: Purpose This study aims to examine the relationship between an ownership structure with multiple large shareholders and corporate social responsibility (CSR) with regard to Chinese-listed companies. Design/methodology/approach Multiple regression analysis was used on 4,940 samples of 884 listed companies in China for the period 2009–2017, to empirically test the influence of an ownership structure on enterprises’ fulfillment of social responsibility. Moreover, the propensity score matching–difference in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Specifically, our study contributes to the growing discussion on the effect of the organization's individual level on CSR [10,11]. In contrast to previous studies pertaining to CSR in employee characteristics [60,61], our study mainly focused on the impact of employee incentives from ESOPs on CSR. We found that compared to firms without ESOPs, firms with ESOPs have higher CSR; this finding is consistent with the results of extant empirical studies [45,52,62], suggesting that through the binding of employee income and corporate interests, ESOPs promote the role of employees as owners and make employees pay more attention to activities related to long-term firm value.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, our study contributes to the growing discussion on the effect of the organization's individual level on CSR [10,11]. In contrast to previous studies pertaining to CSR in employee characteristics [60,61], our study mainly focused on the impact of employee incentives from ESOPs on CSR. We found that compared to firms without ESOPs, firms with ESOPs have higher CSR; this finding is consistent with the results of extant empirical studies [45,52,62], suggesting that through the binding of employee income and corporate interests, ESOPs promote the role of employees as owners and make employees pay more attention to activities related to long-term firm value.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to Khan and Sukhotu (2020) , this article defines media exposure as the number of times observations appear in both print and electric media. Since few people have studied the media exposure on TMTs, this article refers to the definition of CEO media exposure in Godos-Díez et al (2020) and Wang et al (2020) combined with the actual situation of China and the availability of data, TMTs are defined as the number of times TMTs appear on the print and internet media. The natural logarithm of “1++total TMT internet media coverage+total TMT press media coverage” is used to measure the overall media exposure of the TMTs (Media_total), while the natural logarithm of “1+total TMT internet media coverage” is used to measure the exposure of the TMTs in emerging online media (Media_net).…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, internal governance structure affects the participation of CSR. Wang et al (2020) found that the ownership structure of multiple major shareholders is an effective internal governance mechanism. Specifically, the ownership structure of multiple large shareholders could restrict the controlling shareholders from infringing the interests of minority shareholders, thus promoting social responsibility.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…CSR includes public donation responsibility, environmental governance responsibility, responsibility for employees, consumers, shareholders, education and cultural responsibility. Therefore, fulfilling CSR meets the needs of corporate stakeholders, attracts investment funds for development and ensures the daily operation of enterprises and also promotes the improvement of product quality and value and the development of an environmentally-friendly society (Wang et al , 2020). In addition, CSR can help improve corporate reputation, establish a good brand image and improve consumer satisfaction and loyalty to products.…”
Section: Literature Reviewmentioning
confidence: 99%